Land sharing between cultivated and wild plants: urban gardens as hotspots for plant diversity in cities - Birgit Seitz; Sascha Buchholz; Ingo Kowarik; Johann Herrmann; Leonie Neuerburg; Julian Wendler; Leonie Winker; Monika Egerer (Urban Ecosystems, 2022)
Plant communities in urban gardens consist of cultivated species, including ornamentals and food crops, and wild growing species. Yet it remains unclear what significance urban gardens have for the plant diversity in cities and how the diversity of cultivated and wild plants depends on the level of urbanization. We sampled plants growing within 18 community gardens in Berlin, Germany to investigate the species diversity of cultivated and wild plants. We tested species diversity in relation to local and landscape-scale imperviousness as a measure of urbanity, and we investigated the relationship between cultivated and wild plant species within the gardens. We found that numbers of wild and cultivated plant species in gardens are high – especially of wild plant species – independent of landscape-scale imperviousness. This suggests that all community gardens, regardless of their urban contexts, can be important habitats for plant diversity along with their role in urban food provision. However, the number of all species was negatively predicted by local garden scale imperviousness, suggesting an opportunity to reduce imperviousness and create more habitats for plants at the garden scale. Finally, we found a positive relationship between the number of cultivated and wild growing species, which emphasizes that community gardens present a unique urban ecosystem where land sharing between cultivated and wild flora can transpire. As the urban agriculture movement is flourishing worldwide with gardens continuously and spontaneously arising and dissipating due to urban densification, such botanical investigations can support the argument that gardens are places for the reconciliation of plant conservation and food production.